Features of the high frequency power transformer calculation - Zabarilo, D. A. (Science and Transport Progress, 2013)
Purpose. The windings of power transformers have low resistance value and a most inductance, which reduces the rate of rise of current in the windings. Therefore, when the estimated amount of current is set one should make sure of the possibility of achieving it. As inductance is characterized by a short-circuit voltage, it is necessary to develop a technique for determining the maximum magnitude of the current in the windings of the transformer according to the short-circuit voltage and operating frequency. Methodology. The classical method of calculation of transient processes to determine the value of the transient current of the transformer windings to achieve purpose is used. Findings. The nature of the transient current in the windings of high-frequency transformer, which is powered by a voltage inverter is investigated and analyzed. Originality. The method for determining the maximum amount of current depending on the short-circuit voltage and frequency of the applied voltage with other set-up parameters was proposed. Practical value. The proposed method allows determining the maximum value of the current in the windings of the high-frequency transformer including its RL-parameters. This will let compare the value of a given current with possible depending on short-circuit voltage and frequency of the applied voltage. Research material may be applied for power transformers design.